2018
DOI: 10.1111/joic.12507
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following balloon mitral valvuloplasty in pregnant females with mitral stenosis and significant sub valve disease with severe decompensated heart failure

Abstract: BMV offers substantial improvement in clinical outcomes among pregnant patients with MS and heart failure even with severe sub valve disease. The morality rate among failed was high at 31%. The obstetric outcomes were poor after a failed BMV. Outcomes following balloon mitral valvuloplasty in pregnant females with mitral stenosis and significant sub valve disease with severe decompensated heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“… 10 , 11 , 12 , 13 , 14 However, mortality of 11.4% after BMV has been shown in a high risk cohort of patients who presented with decompensated heart failure during pregnancy. 15 The author in this study found a high Wilkin's score, hypoxia and pulmonary hypertension to be predictors of mortality in these patients.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“… 10 , 11 , 12 , 13 , 14 However, mortality of 11.4% after BMV has been shown in a high risk cohort of patients who presented with decompensated heart failure during pregnancy. 15 The author in this study found a high Wilkin's score, hypoxia and pulmonary hypertension to be predictors of mortality in these patients.…”
Section: Discussionmentioning
confidence: 62%
“…and between 3.3% and 7% patients in previously published studies of non-pregnant population. 15 , 16 , 17 , 18…”
Section: Discussionmentioning
confidence: 99%
“…Three additional studies were identified through reference search of the included studies. Altogether, 21 articles were finally included in the review, after excluding one article from the same author with an overlap in the time period of inclusion of cases 18‐38 . Characteristics of the studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The pooled estimate of PBMV complicated with MR was 12.7% (95% CI 7.3%‐19.1%) (Figure 1A). Following PBMV, 16 cases underwent mitral valve replacement for either acute MR (n = 8) or a failed procedure (n = 8) 19,21,27,38 . Various access site complications, including minor groin hematoma, acute arterial occlusion at the site, femoral artery thrombosis, arteriovenous fistula at the site of puncture and common femoral artery pseudo‐aneurysm were also reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation